Kola Nut and Conflict Resolution Among the Igala People of Kogi State, Nigeria - Joel Abah (Centre for Behaviour and Wellness Advocacy, 2016)
This paper examined Kola nut and Conflict Resolution among the Igala people of Kogi State, Nigeria. In a world ravaged by conflicts, certain Africans have kept the fire of brotherhood, through the breaking and eating of Kola nut. Literatures exist on Conflict Resolution, but no empirical study on the topic in question. The aims are to examine (a) the types of Kola nut cotyledons and its relevance in conflict resolution (b) the myths about Kola nut that enhances conflict resolution, and (c) its role in conflict resolution. The qualitative approach was adopted. The sources of data were primary and secondary. The Primary Sources included 20 oral interviews. Purposive sampling was adopted. Content analysis was used to analyse. The secondary sources included books and an unpublished work. The findings reveal (a) two types of Kola nut, (cola acuminata 0-7 cotyledons and cola nitida 2 cotyledons), (b) As regards the myth, it is used to invite and welcome the ancestors during conflict resolution, whosoever harbours grudges against a neighbour after the kola had been eaten will come under the wrath of the ancestors, and (c) It is the harbinger of peace. In conclusion, peace can only be guaranteed when there is security and justice, which could be embedded in a unifying factor(s), like the kola nut. Any community that finds this generally acceptable factor will experience a considerable level of peace, especially when acculturated into every aspect of the modern conflict resolution mechanisms, putting into consideration the indigenous socio-religious conflict resolution strategies.